Taxes For Dummies - Tyson, Eric (For Dummies, 2021)
Take the anxiety out of tax season and file your return with confidence In Taxes For Dummies, 2022 Edition, you'll get line-by-line advice and plan ahead strategies that take the fear and anxiety out of tax season and save you money now and in the months and years ahead. This completely updated edition includes detailed coverage of the numerous tax bills have passed in recent years. You'll learn everything you need to know to file your own taxes with confidence and intelligently plan year-round tax strategies. In this book, you'll: Discover how to take advantage of every deduction and tax credit that applies to your specific circumstances Learn to navigate the IRS website and the newest versions of the most popular online tax preparation and filing options Understand new retirement account options and the implications of new foreign taxation rules Plan ongoing, multi-year tax strategies that will help you achieve your financial goals at every stage of your life Taxes For Dummies, 2022 Edition is the perfect resource for any United States taxpayer planning to file their own 2021 taxes. Whether you're a first-time taxpayer, an expat filing from outside the US, or a seasoned veteran of tax season looking for the latest deductions and strategies to reduce your tax bill, this book is a must-read resource that'll transform how you think about taxes.